B cell depletion impairs vaccination-induced CD8+ T cell responses in a type I interferon-dependent manner. Issue 12 (5th July 2021) - Graalmann, Theresa; Borst, Katharina; Manchanda, Himanshu; Vaas, Lea; Bruhn, Matthias; Graalmann, Lukas; Koster, Mario; Verboom, Murielle; Hallensleben, Michael; Guzmán, Carlos Alberto; Sutter, Gerd; Schmidt, Reinhold E; et al.
Abstract : Objectives: The monoclonal anti-CD20 antibody rituximab is frequently applied in the treatment of lymphoma as well as autoimmune diseases and confers efficient depletion of recirculating B cells. Correspondingly, B cell-depleted patients barely mount de novo antibody responses during infections or vaccinations. Therefore, efficient immune responses of B cell-depleted patients largely depend on protective T cell responses. Methods: CD8 + T cell expansion was studied in rituximab-treated rheumatoid arthritis (RA) patients and B cell-deficient mice on vaccination/infection with different vaccines/pathogens. Results: Rituximab-treated RA patients vaccinated with Influvac showed reduced expansion of influenza-specific CD8 + T cells when compared with healthy controls. Moreover, B cell-deficient JHT mice infected with mouse-adapted Influenza or modified vaccinia virus Ankara showed less vigorous expansion of virus-specific CD8 + T cells than wild type mice. Of note, JHT mice do not have an intrinsic impairment of CD8 + T cell expansion, since infection with vaccinia virus induced similar T cell expansion in JHT and wild type mice. Direct type I interferon receptor signalling of B cells was necessary to induce several chemokines in B cells and to support T cell help by enhancing the expression of MHC-I. Conclusions: Depending on the stimulus, B cells can modulate CD8 + T cell responses. Thus, B cell depletion causes a deficiency of de novo antibody responses and affects the efficacy of cellular response including cytotoxic T cells. The choice of the appropriate vaccine to vaccinate B cell-depleted patients has to be re-evaluated in order to efficiently induce protective CD8 + T cell responses.